Performance level discriminative validity of agility tests in youth tennis players - Munivrana, G.; Jelaska, G.; Tomljanovic, M. (Frontiers in Sports and Active Living, 2025)
Introduction: Various studies have shown that the ability to change the direction of movement quickly plays an important role in achieving top performance in tennis. The main goal of this study was to compare different generic and tennis-specific agility tests to determine whether and to what extent they can differentiate youth tennis players in terms of their competitive success and can be used as a tool to identify talented players in youth tennis categories.